Effects of sewer biofilms on the degradability of carbapenems in wastewater using laboratory scale bioreactors. (15th April 2023) - Sharma, Elipsha; Sivakumar, Muttucumaru; Kelso, Celine; Zhang, Shuxin; Shi, Jiahua; Gao, Jianfa; Gao, Shuhong; Zhou, Xu; Jiang, Guangming
Highlights: UHPLC-MS/MS method developed and validated for carbapenems from urban wastewater. Degradation studied in laboratory scale RM, GS and CTL bioreactors. Significant degradation observed in RM/GS (60–80%) vs. CTL (5–15%). Statistical differences between degradation in RM/GS/CTL evaluated. Role of biofilm in degradation established. Abstract: Carbapenems are last-resort antibiotics used to treat bacterial infections unsuccessfully treated by most common categories of antibiotics in humans. Most of their dosage is secreted unchanged as waste, thereby making its way into the urban water system. There are two major knowledge gaps addressed in this study to gain a better understanding of the effects of their residual concentrations on the environment and environmental microbiome: development of a UHPLC-MS/MS method of detection and quantification from raw domestic wastewater via direct injection and study of their stability in sewer environment during the transportation from domestic sewers to wastewater treatment plants. The UHPLC-MS/MS method was developed for four carbapenems: meropenem, doripenem, biapenem and ertapenem, and validation was performed in the range of 0.5–10 μg/L for all analytes, with limit of detection (LOD) and limit of quantification (LOQ) values ranging from 0.2–0.5 μg/L and 0.8–1.6 μg/L respectively. Laboratory scale rising main (RM) and gravity sewer (GS) bioreactors were employed to culture mature biofilms with real wastewater as the feed. Batch tests were conducted in RM and GS sewer bioreactors fed with carbapenem-spiked wastewater to evaluate the stability of carbapenems and compared against those in a control reactor (CTL) without sewer biofilms, over a duration of 12 h. Significantly higher degradation was observed for all carbapenems in RM and GS reactors (60 – 80%) as opposed to CTL reactor (5 – 15%), which indicates that sewer biofilms play a significant role in the degradation. First order kinetics model was applied to the concentration data along with Friedman's test and Dunn's multiple comparisons analysis to establish degradation patterns and differences in the degradation observed in sewer reactors. As per Friedman's test, there was a statistically significant difference in the degradation of carbapenems observed depending on the reactor type ( p = 0.0017 – 0.0289). The results from Dunn's test indicate that the degradation in the CTL reactor was statistically different from that observed in either RM ( p = 0.0033 – 0.1088) or GS ( p = 0.0162 – 0.1088), with the latter two showing insignificant difference in the degradation rates observed ( p = 0.2850 – 0.5930). The findings contribute to the understanding about the fate of carbapenems in urban wastewater and the potential application of wastewater-based epidemiology. Graphical abstract: Image, graphical abstract